Profile changes and stability following distraction osteogenesis with rigid external distraction in adult cleft lip and palate deformities - Jaeson M Painatt; Ravi Veeraraghavan; Ushass Puthalath; Sherry Peter; Latha P Rao; Maria Kuriakose (Wolters Kluwer Medknow Publications, 2017)
Objectives: The objective of this study is to analyze the hard and soft-tissue profile changes as well as the upper airway changes after distraction osteogenesis (DO) using rigid external distraction device in adult cleft lip and palate (CLP) patients. The study also evaluates the stability of the surgical result. Materials and Methods: Three lateral cephalometric radiographs were taken: Predistraction (T1), postdistraction (T2), and 1 year after distractor removal (T3). The treatment changes (T1 vs. T2) and the stability (T2 vs. T3) were analyzed. The overall treatment changes after 1 year were also evaluated (T1 vs. T3). The lateral cephalograms were digitally analyzed with the help of software named Dolphin. Statistical Analysis Used: Wilcoxon Signed-Ranks test was used, and the probability value (P value) of 0.05 was considered as statistically significant level. Results: Eleven adult patients with CLP were retrospectively analyzed. After distraction, there was a significant mean maxillary advancement of 14 mm (P < 0.01) from a T1 value of 73.54 ± 10.38 to a T2 value of 88.2 ± 10.49. The lower facial height and the incisor exposure were significantly increased. The nasolabial angle had a significant improvement of 24.5° (P < 0.01) from a T1 value of 56.6 ± 21.03 to a T2 value of 81.18 ± 14.4.The upper airway was significantly improved by 3.7 mm (P < 0.01) with a T1 value of 13.5 ± 3.8 to a T2 value of 17.2 ± 3.66. After 1-year follow-up, there was a significant maxillary relapse of 3.20 mm (P < 0.05) from a T2 value of 8.29 ± 6.84 to a T3 value of 5.09 ± 5.59. However, the soft-tissue profile and upper airway remained stable. Conclusion: The clinician should have an understanding of the related hard and soft tissues as well as airway changes which may assist him when planning for maxillary advancement for CLP patients with DO. There were significant improvements immediately after distraction, but during the 1-year follow-up, some relapse was seen. This stressed on the need for overcorrection of about 35%-40% for adult CLP patients.